Therapeutic effects of turmeric or curcumin extract on pain and function for individuals with knee osteoarthritis: a systematic review. Issue 1 (13th January 2021) - Paultre, Kristopher; Cade, William; Hernandez, Daniel; Reynolds, John; Greif, Dylan; Best, Thomas Michael
Abstract : Purpose: To determine whether supplementation with turmeric or curcumin extract effects pain and physical function in individuals with knee osteoarthritis (OA). Second, we investigated the therapeutic response (pain and function) of turmeric compared with non-steroidal anti-inflammatory drugs (NSAIDs). Methods: A search was conducted in MEDLINE, Embase, CINAHL and Cochrane Review. Inclusion criteria included randomised controlled trials reporting pain and physical function in humans with knee OA comparing turmeric therapy with NSAIDs or no therapy. Two reviewers screened 5273 abstracts. Risk of bias and quality were assessed via Cochrane Collaboration tool and CONSORT (Consolidated Standards of Reporting Trials) 2010, respectively. Results: Ten studies were included in the final analysis. Eight had high methodological quality and two were categorised as good with a mean CONSORT quality score of 21.1. Nine studies had adequate sequence generation and six had adequate allocation concealment. Participants and outcome assessors were blinded in eight studies. Three of the studies compared turmeric therapy to NSAIDs. All 10 studies showed improvement in pain and function from baseline with turmeric therapy (p≤0.05). In three studies comparing turmeric to NSAIDs, there were no differences in outcome scores (p>0.05). In all studies there were no significant adverse events in the turmeric therapy group. Conclusion: Compared with placebo, there appears to be a benefit of turmeric on knee OA pain and function. Based on a small number of studies the effects are similar to that of NSAIDs. Variables such as optimal dosing, frequency and formulation remain unclear at this time.